2012
DOI: 10.1158/1078-0432.ccr-11-2725
|View full text |Cite
|
Sign up to set email alerts
|

High-Risk Ovarian Cancer Based on 126-Gene Expression Signature Is Uniquely Characterized by Downregulation of Antigen Presentation Pathway

Abstract: Purpose: High-grade serous ovarian cancers are heterogeneous not only in terms of clinical outcome but also at the molecular level. Our aim was to establish a novel risk classification system based on a gene expression signature for predicting overall survival, leading to suggesting novel therapeutic strategies for high-risk patients.Experimental Design: In this large-scale cross-platform study of six microarray data sets consisting of 1,054 ovarian cancer patients, we developed a gene expression signature for… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
187
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 160 publications
(193 citation statements)
references
References 39 publications
6
187
0
Order By: Relevance
“…first a MAS5 algorithm-based normalization on individual-chip level and a second scaling normalization to set the average expression on each chip to 1,000. 39 For the 'validation dataset' analysis, the cohorts consisting of >250 patients each for breast cancer (n D 285; GSE2034), 53 non-small cell lung cancer (n D 274; GSE41271) 54,55 and ovarian cancer (n D 259; GSE32062) 56 were analyzed as described above, using the PROGgeneV2 platform. 57 The available clinicopathological characteristics of the patients in these respective 'validation' cohorts are described in Table S2.…”
Section: Meta-analysis 'Pipeline' Descriptionmentioning
confidence: 99%
“…first a MAS5 algorithm-based normalization on individual-chip level and a second scaling normalization to set the average expression on each chip to 1,000. 39 For the 'validation dataset' analysis, the cohorts consisting of >250 patients each for breast cancer (n D 285; GSE2034), 53 non-small cell lung cancer (n D 274; GSE41271) 54,55 and ovarian cancer (n D 259; GSE32062) 56 were analyzed as described above, using the PROGgeneV2 platform. 57 The available clinicopathological characteristics of the patients in these respective 'validation' cohorts are described in Table S2.…”
Section: Meta-analysis 'Pipeline' Descriptionmentioning
confidence: 99%
“…(Yoshino et al, 2011) Microarray datasets have also been widely used in discovering tumor types and tumor progression by comparing different stages of tumors (Privette Vinnedge et al, 2011;Yeoh et al, 2010). Moreover, some studies developed a gene expression signature for predicting overall survival of lung cancer with microarray data sets (Yoshihara et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Many early generation ovarian cancer gene expression profiling studies focused primarily on the prognostic value of gene expression signatures. Results of these early prognostic gene expression studies [6][7][8][9][10][11][12][13][14] and those following [15][16][17][18][19][20][21][22][23][24][25] are summarized in Table 1 (Table 1). Most of these studies have identified a group of prognostically relevant genes in relatively small training sets but did, to their credit, validate the prognostic relevance of the respective gene signatures in independent cohorts.…”
Section: Gene Expression Signatures With Prognostic Relevancementioning
confidence: 99%
“…The ovarian cancer analysis showed a wide range of accuracy of published prognostic models and signatures. The top-ranked three models were those of the TCGA consortium [18,23], a signature by Yoshihara et al [20] and one by Bonome et al (optimally debulked patients) [10]. These achieved summary C-indices between 0.57 and 0.60.…”
Section: Gene Expression Signatures With Prognostic Relevancementioning
confidence: 99%